Broadband circularly polarised antenna with asymmetric ground and L‐shaped strips. Issue 23 (1st November 2014) - Zhang, Huan; Jiao, Yong‐Chang; Ni, Tao; Liang, Wei‐Long
Abstract : A novel broadband circularly polarised antenna fed by a coplanar waveguide (CPW) is proposed. Two L‐shaped grounded strips and an asymmetrical ground are utilised to achieve the broadband circular polarisation (CP) feature. The measured results show that the 10 dB impedance bandwidth of the antenna is 2.01 GHz (69.4%, 1.89–3.9 GHz) and the 3 dB axial ratio (AR) bandwidth is 2.1 GHz (72.4%, 1.85–3.95 GHz). The experimental results agree well with the simulated results.